1999
DOI: 10.3109/10673229909017206
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine for Comorbid Substance Use Disorder and Schizophrenia: Do Patients with Schizophrenia Have a Reward-Deficiency Syndrome That Can Be Ameliorated by Clozapine?

Abstract: Alcohol and other drugs of abuse are commonly used by persons with schizophrenia and contribute to the overall morbidity of the disorder. Standard, or typical, antipsychotic drugs do not limit such substance use and may even render it more likely. However, preliminary data from our group and others suggest that the atypical antipsychotic clozapine may decrease substance use in this population. While recognizing the likelihood that substance use decreases negative symptoms (as well as extrapyramidal symptoms) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 77 publications
7
102
2
3
Order By: Relevance
“…The study with olanzapine is consistent with previous work indicating that consumption of alcohol increases craving and that a traditional dopamine antagonist (ie haloperidol), that acts on D 2 and D 4 receptors, reduces alcohol-elicited craving (Modell et al, 1993). In addition to these laboratory studies on dopamine antagonists and alcohol craving, recent clinical reports have suggested that clozapine, a D 4 receptor antagonist that is similar to olanzapine, reduces substance abuse among patients with comorbid substance abuse/ dependence (Green et al, 1999) and specifically, alcohol use (Drake et al, 2000). Thus, research with humans suggests that selective targeting of dopamine receptor subtypes may be useful for developing pharmacotherapies that reduce craving.…”
Section: Introductionsupporting
confidence: 87%
“…The study with olanzapine is consistent with previous work indicating that consumption of alcohol increases craving and that a traditional dopamine antagonist (ie haloperidol), that acts on D 2 and D 4 receptors, reduces alcohol-elicited craving (Modell et al, 1993). In addition to these laboratory studies on dopamine antagonists and alcohol craving, recent clinical reports have suggested that clozapine, a D 4 receptor antagonist that is similar to olanzapine, reduces substance abuse among patients with comorbid substance abuse/ dependence (Green et al, 1999) and specifically, alcohol use (Drake et al, 2000). Thus, research with humans suggests that selective targeting of dopamine receptor subtypes may be useful for developing pharmacotherapies that reduce craving.…”
Section: Introductionsupporting
confidence: 87%
“…These characteristics support inclusion of schizophrenia within the spectrum of the 'reward deficiency syndrome' (Green et al, 1999), which is comprised of a broad range of personality traits and mental disorders (including, but not limited to schizoid/ avoidant character styles, glucose binging and posttraumatic stress disorder) allegedly characterized by hypofunctionality of the reward circuitry, clinically manifested as diminution of drive/motivation and of capacity to enjoy or to experience pleasure (Comings and Blum, 2000).…”
Section: Key Factors Involved In the Normal Reward Function Are Impaimentioning
confidence: 83%
“…One such possible overlap area is the neural pathways mediating reward (subjective experience of pleasure) and reinforcement (increased rate of recurrent actions), a relevant etiologic factor in both schizophrenia (Green et al, 1999;Chambers et al, 2001;Brady and Sinha, 2005) and eating behavior (Wang et al, 2001(Wang et al, , 2002(Wang et al, , 2003(Wang et al, , 2004. The following sections discuss energy balance systems and how they intersect with the brain reward and reinforcement mechanisms.…”
Section: Dietary Habits Of Schizophrenic Patientsmentioning
confidence: 99%
“…Thus, the effect of alcohol and alcohol cues on the activation of these dopamine pathways represents a target that may prove to be useful in terms of pharmacotherapy development, and genetic variants that alter the functioning of these pathways may prove to be important in terms of predicting the success of such a pharmacotherapy. Other research has suggested that clozapine, a D 4 receptor antagonist that is somewhat similar to olanzapine, reduced substance abuse among patients with comorbid substance abuse/dependence (Green et al, 1999) and, specifically, alcohol use (Drake et al, 2000). Thus, clinical research also supports an important role for the D 2 family of receptors, and specifically the D4 receptor.…”
Section: Introductionmentioning
confidence: 91%